HUBUNGAN KEBUTUHAN SPIRITUAL DENGAN KUALITAS HIDUP LANSIA KOMUNITAS MUSLIM RW 006 KELURAHAN PONDOK KACANG TIMUR KECAMATAN PONDOK AREN TANGERANG SELATAN TAHUN 2020 - Vebry Haryati Lubis; Novianti; Peters Martungkar Simanjuntak (Jurnal Kesehatan STIKes IMC Bintaro, 2020)
Spiritual needs in old age are the need to fulfill comfort, maintain bodily functions and help to deal with death calmly and peacefully. Quality of life is an individual's perception of their benefits in life. This study aims to determine the relationship between spiritual needs and the quality of life of the elderly Muslim community RW 006, Pondok Kacang Timur Village, South Tangerang. The research used is quantitative non-experimental. This research method uses a cross sectional approach. The sample in this study amounted to 60 people with quota sampling technique. Data analysis techniques using univariate and bivariate analysis. Statistical tests using the Chi Square test. The results showed that respondents with spiritual needs were met and had a good quality of life for the elderly were 22 respondents (73.3%) and 8 respondents (26.7%) showed the quality of life of the elderly was not good. The results for respondents who have spiritual needs are not met and the quality of life of the elderly is good as many as 12 respondents (40%) and 18 respondents (60%) indicate the quality of life of the elderly is not good. The results of this study indicate that there is a significant relationship between spiritual needs with the quality of life of the elderly by showing the p value is 0.009 or p <0.05. In conclusion the elderly are advised to participate actively in religious activities and health service activities in order to be able to maintain their physical health conditions so that the quality of life improves.